Technical and economic analysis of recovery systems for pastures with Urochloa brizantha CV. Marandu - Barbieri, Rayner Sversut; Troleis, Maria Julia Betiolo [UNESP]; Souza, Paulino Taveira de [UNESP]; Rodrigues, Bruno Henrique Volpato [UNESP]; Sabbag, Omar Jorge [UNESP]; Montanari, Rafael [UNESP] (Centro Universitario de Maringa, 2022)
Pasture recovery by the re-composition of soil fertility has low operational costs, although studies are required to compare it to application systems at variable rates within planning and development of a region. Research evaluates economically the recovery of soil fertility of a degraded pasture in two production systems: the conventional system (CS) and precision agriculture (PA), by simulation, with estimate of costs and respective rentability coupled to recovery practices in Selvíria MS Brazil. A bio-economic simulation was employed and costs were classified according to the methodology of the Institute of Agricultural Economy of São Paulo. CS and PA recovery showed 5.41% and 6.42% gain respectively, with cost price @-1 of R$205.96 and R$203.54 for CS and PA, respectively. Due to valorization of @ during the last year, both systems revealed a feasible economic return according to the estimates given. When regions cultivated with PA and CS are compared, probably more reliable results are obtained coupled to better perspectives in larger areas.
Análise técnico-econômica de sistemas de recuperação de pastagens de Urochloa brizantha CV. Marandu
Keywords: Brachiaria; Conservation; Costs; Spatial variability; Technology